The Liability of Cosmetics Business Operators For The Impact of Hazardous Product: Pinkflash Cosmetics Brand on Consumers - Farbadi, Mayla Putri; Suherman (Dinasti Research, 2025)
Consumer protection in the cosmetics industry is a very important aspect in realizing justice, safety, and legal certainty, especially when dangerous products can threaten public health. This article aims to analyze the legal responsibilities of cosmetics businesses and the legal protection provided to consumers in the case of Pinkflash products containing dangerous ingredients such as mercury and hydroquinone. The research method used is normative legal research with a legislative, conceptual, and case approach. The results show that cosmetic businesses bear civil, criminal, and administrative legal responsibility, including the obligation to compensate consumers, criminal sanctions in the form of imprisonment and fines, and administrative sanctions in the form of product recalls and revocation of distribution permits by the Indonesian Food and Drug Administration (BPOM). Legal protection for consumers is carried out preventively through product supervision and distribution permits, as well as repressively through the application of the principle of strict liability, legal sanctions, and dispute resolution through the Consumer Dispute Settlement Agency (BPSK). Although the legal framework in Indonesia is comprehensive, its implementation is still weak due to a lack of post-distribution supervision and low consumer awareness. Therefore, improved coordination between institutions and public education are needed to achieve effective consumer protection.